The Structural and Surface Morphology Properties of Aluminum Doped CdO Thin Films Prepared by Vacuum Thermal Evaporation Technique. - Shehab, Alia A.; Maki, Samir A.; Salih, Ayad A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Undoped and Al-doped CdO thin films have been prepared by vacuum thermal evaporation on glass substrate at room temperature for various Al doping ratios (0.5, 1 and 2)wt.% . The films are characterized by XRD and AFM surface morphology properties. XRD analysis showed that CdO:Al films are highly polycrystalline and exhibit cubic crystal structure of lattice constant averaged to 0.4696 nm with (111) preferred orientation. However, intensity of all peaks rapidly decreases which indicates that the crystallinity decreases with the increase of Al dopant. The grain size decreases with Al content (from 60.81 to 48.03 nm). SEM and AFM were applied to study the morphology and to estimate the surface roughness of the obtained films. All films were homogeneous and smooth, with a characteristic spherical grain size depending on Al content. The (RMS) roughness of the films increases with the increase of Al dopant. The improvement of the structural and surface morphology properties of Al-doped CdO has potential applications for different optoelectronic device applications.